A Retrospective Review of Paediatric Non-Infectious Uveitisin Cape Town: Disease Characteristics and Outcomes on Immunomodulating Treatment - Slamang, Waheba (Department of Paediatrics and Child Health, 2021)
Background Uveitis is a known cause of blindness in the developed world, where non-infectious diseases dominate the spectrum of underlying aetiologies. However, data from sub-Saharan Africa is lacking. Here we aim to describe the diseases associated with non-infectious uveitis and the impact of currently available treatment in this setting. Methods A retrospective observational analysis of children with non-infectious uveitis from January 2010 to December 2017, attending the tertiary paediatric rheumatology and ophthalmology referral units in Cape Town was conducted. Statistical analysis utilising STATA13 software was performed with p < 0.05 considered significant. Results Twenty-nine children were identified with a median age at first visit of 74 months (IQR 49–86 months), female to male ratio of 0.9:1, predominantly of mixed race (72.4%). Juvenile idiopathic arthritis associated uveitis (JIAU) (48.3%) was the most frequent diagnosis. All children with JIAU had chronic anterior uveitis and 3 (21.4%) presented with uveitis before arthritis. There were no differences between children with uveitis and those with arthritis only, for gender (p = 0.68) and race (p = 0.58) but significantly, children with uveitis presented at an overall younger age (p = 0.008), with antinuclear antibody positive (p < 0.001) oligo-articular JIA (p = 0.01) and older age appeared to be protective (p = 0.01 OR1.0 CI 0.6-1.7). Children with idiopathic uveitis (41.4%) were predominantly male (66.6%), of mixed race (75%), with chronic anterior uveitis (41.7%) and presented with cataracts (100%). Less commonly, sarcoidosis (6.9%) and Behcet's disease (3.5%) were diagnosed. 55.2% had complications at presentation, predominantly cataracts (87.5%). 19 children (65.5%) had inactive disease at 12 months from diagnosis and remission as assessed at the last clinical visit, was achieved in 58.6% on standard initial therapy and in 75% of those on tumour necrosis factor inhibitors. Surgery was needed in 41.4%, primarily in the idiopathic group. Visual acuity improved or was maintained on treatment. Conclusion The spectrum and characteristics of immune mediated non-infectious uveitis are comparable to that reported in developed countries. Current practice detects children with potentially sight-threatening disease and access to tumour necrosis factor inhibitors has improved outcomes in refractory cases.